Zotero Training in Improving Student Knowledge and Writing Skills - Baroroh, Umi; Sabarudin, Sabarudin; Mahariah, Mahariah; Bayu, Krisna (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the implementation of the Zotero application to increase knowledge and skills in writing papers in class 1A PAI FITK UIN North Sumatra Medan. The approach in this research is qualitative. Data is from observation notes, questionnaire results, and interview notes. Data sources are students as respondents in this study. Data collection techniques are observation, documentation, and unstructured interviews. Data analysis techniques are carried out by condensing data activities, displaying data, and drawing conclusions. The training results show first, application usage training provides benefits in the form of new knowledge for students. This can be seen from the number of students who have never used as many as 39 students after training there. Thirty-six students have practiced how to use the Zotero application. Second, the training activities increased students' writing skills, with indicators of 23 people being quite capable, 13 people capable, and four very capable. Increased knowledge and skills can also be seen from the positive impressions written by students on Google Forms after attending the training. This study concluded that students who previously did not know and could not operate knew and could operate. Reference management training needs to be given to new students for quality scientific writing.